Overcoming the blood-brain barrier?: Prediction of blood-brain permeability of hydrophobically modified polyethylenimine polyplexes for siRNA delivery into the brain with in vitro and in vivo models - Hartl, Natascha Verena; Gabold, Bettina; Adams, Friederike; Uhl, Philipp; Oerter, Sabrina; Gätzner, Sabine; Metzger, Marco; König, Ann-Christine; Hauck, Stefanie M.; Appelt-Menzel, Antje; Mier, Walter; Fricker, Gert; et al. (Journal of controlled release, 2023)
The blood-brain barrier (BBB) is a highly selective biological barrier that represents a major bottleneck in the treatment of all types of central nervous system (CNS) disorders. Small interfering RNA (siRNA) offers in principle a promising therapeutic approach, e.g., for brain tumors, by downregulating brain tumor-related genes and inhibiting tumor growth via RNA interference. In an effort to develop efficient siRNA nanocarriers for crossing the BBB, we utilized polyethyleneimine (PEI) polymers hydrophobically modified with either stearic-acid (SA) or dodecylacrylamide (DAA) subunits and evaluated their suitability for delivering siRNA across the BBB in in vitro and in vivo BBB models depending on their structure. Physicochemical characteristics of siRNA-polymer complexes (polyplexes (PXs)), e.g., particle size and surface charge, were measured by dynamic light scattering and laser Doppler anemometry, whereas siRNA condensation ability of polymers and polyplex stability was evaluated by spectrophotometric methods. The composition of the biomolecule corona that absorbs on polyplexes upon encountering physiological fluids was investigated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and by a liquid chromatography-tandem mass spectrometry (LC-MS-MS) method. Cellular internalization abilities of PXs into brain endothelial cells (hCMEC/D3) was confirmed, and a BBB permeation assay using a human induced pluripotent stem cell (hiPSC)-derived BBB model revealed similar abilities to cross the BBB for all formulations under physiological conditions. However, biodistribution studies of radiolabeled PXs in mice were inconsistent with in vitro results as the detected amount of radiolabeled siRNA in the brain delivered with PEI PXs was higher compared to PEI-SA PXs. Taken together, PEI PXs were shown to be a suitable nanocarrier to deliver small amounts of siRNA across the BBB into the brain but more sophisticated human BBB models that better represent physiological conditions and biodistribution are required to provide highly predictive in vitro data for human CNS drug development in the future.